Hubungan Pendidikan Dan Usia Terhadap Pengetahuan Pasangan Usia Subur Tentang Persiapan Kehamilan Di Desa Tuksongo Borobudur - Heny Kristanty; Eka Vicky Yulivantina; Siti Fadhilah (Nan Tongga Health And Nursing, 2026)
Ensuring a healthy pregnancy is an important responsibility for couples in maintaining the health of future children. Data from the 2023 Indonesian Health Survey shows that pregnancy risk factors among women aged 10–54 years in Central Java reached 27.8%, which is higher than the national average of 15.6%. Knowledge about pregnancy preparation—such as adequate nutritional intake, medical consultations, and pregnancy planning—is essential for reducing these risks. Education and age are considered important factors that may influence the level of knowledge among reproductive-age couples. This study aimed to determine the relationship between education level and age with the knowledge of reproductive-age couples (PUS) regarding pregnancy preparation in Tuksongo Village, Borobudur. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 66 couples of reproductive age (132 respondents) selected using total sampling in Tuksongo Village, Borobudur. Data were collected using a true–false questionnaire containing 26 statements that had been tested for validity and reliability. Data analysis was conducted using Fisher’s Exact test. The majority of respondents had secondary education (53% of males and 56.1% of females) and were aged 20–25 years (66.7% of males and 87.9% of females). Most respondents demonstrated good knowledge regarding pregnancy preparation (84.8% of males and 89.4% of females). The analysis showed a significant relationship between education level and knowledge of pregnancy preparation among reproductive-age couples (p = 0.002; p < 0.05). However, age was not significantly associated with knowledge (p = 0.537; p > 0.05). Education is significantly associated with knowledge regarding pregnancy preparation among reproductive-age couples, while age does not show a significant relationship. Strengthening educational exposure may improve awareness and knowledge related to healthy pregnancy preparation.